Dissociable Effects of Endogenous and Exogenous Attention on Crowding: Evidence from Event-Related Potentials - Mingliang Gong; Tingyu Liu; Yingbing Chen; Yingying Sun (Brain Sciences)
Background/Objectives: Crowding is a common visual phenomenon that can significantly impair the recognition of objects in peripheral vision. Two recent behavioral studies have revealed that both exogenous and endogenous attention can alleviate crowding, but exogenous attention seems to be more effective. Methods: The present study employed the event-related potential (ERP) technique to explore the electrophysiological characteristics of the influence of these two types of attention on crowding. In the experiment, participants were required to judge whether the letter “T” was upright or inverted, which may be preceded by an exogenous cue or an endogenous cue indicating the location of the target letter. Results: The behavioral results showed that while exogenous cues reduced crowding in all stimulus onset asynchronies (SOAs), endogenous attention took effects only in long SOA. The ERP results indicated that both endogenous and exogenous cues significantly alleviated the inhibition of visual crowding on the N1 component. However, the endogenous cue was effective only under long SOA, while the exogenous cue was effective only under short SOA conditions. In addition, invalid exogenous cues induced a larger P3 wave amplitude than valid ones in the short SOA condition, but endogenous attention did not show such a difference. Conclusions: These results indicate that both endogenous and exogenous attention can alleviate the effects of visual crowding, but they differ in effect size and temporal dynamics.